2008
DOI: 10.4049/jimmunol.181.11.7489
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Induce Apoptosis in Tubular Epithelial Cells and Contribute to Renal Ischemia-Reperfusion Injury

Abstract: Renal ischemia-reperfusion injury (IRI) can result in acute renal failure with mortality rates of 50% in severe cases. NK cells are important participants in early-stage innate immune responses. However, their role in renal tubular epithelial cell (TEC) injury in IRI is currently unknown. Our data indicate that NK cells can kill syngeneic TEC in vitro. Apoptotic death of TEC in vitro is associated with TEC expression of the NK cell ligand Rae-1, as well as NKG2D on NK cells. In vivo following IRI, there was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(150 citation statements)
references
References 57 publications
4
143
1
2
Order By: Relevance
“…Blockade of TLR2, however, has recently been tested in humans and is in phase 2 trials in the United States and Europe (OPN-305; Opsona Therapeutics). 31 Virtually all immune cells have been implicated in AKI, and some are thought to be deleterious (e.g., neutrophils, 10,16 monocytes/macrophages, 25,32 DCs, 33,34 NKT cells, 17,35 NK cells, 19 and B cells 18,36 ), whereas others are likely protective (e.g., Tregs 20,21 ). Others, such as macrophages, play different roles depending on the type and time at which they arrive in the injured tissue.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockade of TLR2, however, has recently been tested in humans and is in phase 2 trials in the United States and Europe (OPN-305; Opsona Therapeutics). 31 Virtually all immune cells have been implicated in AKI, and some are thought to be deleterious (e.g., neutrophils, 10,16 monocytes/macrophages, 25,32 DCs, 33,34 NKT cells, 17,35 NK cells, 19 and B cells 18,36 ), whereas others are likely protective (e.g., Tregs 20,21 ). Others, such as macrophages, play different roles depending on the type and time at which they arrive in the injured tissue.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
“…6,11 However, responses of almost equal rapidity occur from the bloodstream involving endothelial adherence and activation of neutrophils and monocytes as well as intraparenchymal infiltration by neutrophils, monocytes, effector memory T cells, and other less frequent myeloid and lymphoid effectors. 6,[15][16][17][18][19] The initial activation-induced responses of these resident and recruited immune cells are typically dominated by the production of archetypal proinflammatory mediators (cytokines, chemokines, enzymes, free radical species, and lipid mediators) with high cytotoxic potential, which tend to amplify and extend cell damage and cell death. 4,6 In this manner, the phase of acute inflammatory response may be seen as consolidating and worsening organ dysfunction after injury.…”
Section: Basic Concepts Of Inflammationmentioning
confidence: 99%
“…Slides were scored by a pathologist in a blinded fashion (0: no change, 1þ: <25% area change, 2þ: 25-50% area change, 3þ: 50-75% area change, 4þ: 75% area change) (34,36). Criteria for allograft injury included endothelial cell damage, infarction, lymphocyte infiltrate, fibrosis, thrombosis, hemorrhage and myocyte damage.…”
Section: Histology and Immunohistochemistrymentioning
confidence: 99%
“…IRI induced the expression of an NK cell-activating ligand (Rae-1) on tubule epithelial cells (TECs) and in vitro studies demonstrated that the interaction of the NKG2D receptor on NK cells with Rae-1 on TECs causes perforin-dependent lysis of cultured kidney cells. Antibody-mediated depletion of NK cells inhibited IRI in wild-type (WT) mice and adoptive transfer of WT, but not perforin KO, NK cells into a T, B and NK cell-deficient mouse enhanced IRI (Zhang et al, 2008).…”
Section: Natural Killermentioning
confidence: 99%